Active Acoustic Systems for the Control of Room Acoustics. (April 2013) - Poletti, M. A.
The acoustic design of auditoria involves the specification of the room geometry and boundary properties, and any additional acoustic elements such as reflectors or diffusers, to usefully direct sound to produce a desired subjective experience, quantified by measurable acoustic parameters. This design must take into account the reflection of sound within the stage area, the early reflections from the stage to the audience and the reverberant response of the room. The sound produced by the audience can also be an important consideration. Active acoustic systems provide an alternative approach to controlling subjective experience. They use microphones, electronic processors and loudspeakers to create reflections and reverberation in addition to those produced by the naturally-occurring sound field. The acoustic properties can be changed instantly, and the enhanced acoustic properties of the auditorium can typically be varied over a wider range than can be produced by variable passive techniques. The design of active acoustics follows that of passive approaches, but rather than the physical arrangement of the room surfaces, it commences with an existing passive space with some minimum acoustic condition, and requires the arrangement of microphones to detect relevant sound and the choice of processors and loudspeaker positions to direct it usefully back into the room to produce a desired set of acoustic parameters. While active systems have historically been developed with the goal of enhancing either the stage or audience sound, they must generally provide the same control of sound as passive acoustic design. This paper discusses the principles of active acoustic systems and how they are used to achieve the required range of control. A survey of current commercial systems is given and some implications for the future of live performance are explored.